Urinary Aspergillosis in a Patient with Systemic Lupus Erythematosus (SLE) - Mayara Gabriele Toledo; Hugo Rodrigues Alves; Isadora Cambruzzi; Laís Lopes Pires; Mariana Rossi; Ana Carolina Gonçalves Brito; Andrea D’Avila Freitas; Natalia Chilinque Zambão da Silva (Case Reports in Infectious Diseases)
Aspergillosis is an opportunistic mycosis that generally affects the lungs. The fungus was cleared by the immune system of a healthy host. Extrapulmonary forms are very rare, and there are few reports of urinary aspergillosis. In this case report, we describe a 62-year-old woman with systemic lupus erythematosus (SLE) with complaints of fever and dysuria. The patient had recurrent episodes of urinary tract infection and several hospitalizations. A computed tomography revealed an amorphous mass in the left kidney and bladder. After partial resection of the material was referred for analysis, Aspergillus infection was suspected and confirmed by culture. Successful treatment with voriconazole was provided. Diagnosis of localized primary renal Aspergillus infection in a patient with SLE requires careful investigation due to its benign presentation and lack of associated systemic clinical features.